Powell-Eyring Fluid Peristaltic Transfer in an Asymmetric Channel and A Porous Medium under the Influence of A Rotation and an Inclined Magnetic Field - Ibraheem, Rana Ghazi; Hummady, Liqaa Zeki (Iraqi Journal of Science, 2023)
In this article, we investigate the peristaltic flow of a Powell-Eyring fluid flowing in an asymmetrical channel with an inclining magnetic field through a porous medium, and we focus on the impact that varying rotation has on this flow. Long wavelength and low Reynolds number are assumed, where the perturbation approach is used to solve the nonlinear governing equations in the Cartesian coordinate system to produce series solutions. Distributions of velocity and pressure gradients are expressed mathematically. The effect of these parameters is discussed and illustrated graphically through the set of figures. To get these numerical results, we used the math program MATHEMATICA.